2015
DOI: 10.1007/s10867-015-9386-z
|View full text |Cite
|
Sign up to set email alerts
|

Energy patterns in twist-opening models of DNA with solvent interactions

Abstract: Energy localization, via modulation instability, is addressed in a modified twistopening model of DNA with solvent interactions. The Fourier expansion method is used to reduce the complex roto-torsional equations of the system to a set of discrete coupled nonlinear Schrödinger equations, which are used to perform the analytical investigation of modulation instability. We find that the instability criterion is highly influenced by the solvent parameters. Direct numerical simulations, performed on the generic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Indeed, the breaking of the hydrogen bonds starts with slight oscillations of the bases and then grow progressively in amplitude under the action of RNA-polymerase till the breaking of the hydrogen bond, condition for the genetic information to be collected by the messenger-RNA. This suggest the presence of many modes that contribute to collect such an energy, leading to some modification of the way DNA strands breathe [21][22][23]. For example, the single mode here displays one-humped oscillatory structures (Figure 2a), while trains of multibreather elements correspond to the coupled mode (Figure 2b).…”
Section: Amplitude Equationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, the breaking of the hydrogen bonds starts with slight oscillations of the bases and then grow progressively in amplitude under the action of RNA-polymerase till the breaking of the hydrogen bond, condition for the genetic information to be collected by the messenger-RNA. This suggest the presence of many modes that contribute to collect such an energy, leading to some modification of the way DNA strands breathe [21][22][23]. For example, the single mode here displays one-humped oscillatory structures (Figure 2a), while trains of multibreather elements correspond to the coupled mode (Figure 2b).…”
Section: Amplitude Equationsmentioning
confidence: 94%
“…However, recent developments have shown that when the hydrogen bond stretching is effective, the solvent molecules present in the DNA environment stabilize the molecule in the opened configuration [21,29,30] in order to prevent the molecule from re-closing. We should therefore modify the present model by taking accounts of these effects which could enrich our investigations on the most realistic profile of transcription and replication eye-like structures.…”
Section: The Mixed Solutionsmentioning
confidence: 99%